Household Water Usage and Irrigation Practices - Hayk Khachatryan; Alicia Rihn; Michael Dukes (EDIS)
Water pollution and drought in the United States have made water scarcity a widespread concern. Currently, residential consumers account for most urban water use, and meaningful programs that lead to water conservation rely on a comprehensive understanding of how consumers use water inside and outside their homes. This 5-page fact sheet outlines University of Florida researchers’ assessments of current US household indoor and outdoor water use to assist policy makers and researchers with creating incentives for homeowners to conserve water. Written by Hayk Khachatryan, Alicia Rihn, and Michael Dukes, and published by the Department of Food and Resource Economics, September 2016.